Global logistics network design problem with rules of origin - Shunichi Ohmori; Qian Huang; Kazuho Yoshimoto (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: This paper aims to incorporate rules of origin into international taxation into firms' global operations. The purposes of this research are to develop a new model for the global logistics network design of an assembly system with rules of origin and to analyze how the changes of international relationships will affect logistics network design and evaluation functions. Design/methodology/approach: In this study, we develop a global logistics network design model prescribing allocating amounts for production, assembly, and distribution. A path-based programming model is presented that represents the complexities associated with international and interenterprise issues. The objective is to minimize total costs, which are costs of production, assembly, transportation, and customs duties. In addition to customs duties, rules of origin, which were, not addressed in previous studies, are considered. Several computational experiments with industrial examples are presented to validate the model. Findings: The results indicate that the tax planning and alignment with the FTA might have a significant impact on the decision-making in the global supply chain for multi-national operating companies. Therefore, the multi-national operating companies need to be aware of importance of what-if simulation before or after FTA changes. Originality/value: While designing global supply chain, the tax effects and use of free-trade agreements (FTAs), were generally omitted. In this paper, we proposed a global logistics network design model with rules of origin. We show the effectiveness and necessity to consider rules of origin. This model can be used in making an optimal global logistics network for global companies. The results of this model are used as a target for a real optimal logistics network. Companies can make a better logistics network by using this model.
Keywords: 650; Global logistics network design; global supply chain; rules of origin; free trade agreement